(untitled) (Journal of Global Arts Studies, 2025)
Background： Gu embroidery, as a traditional embroidery craft in China, stands out in the rich and diverse intangible cultural heritage of China with its unique artistic charm and long historical heritage, highlighting the splendid glory of Chinese embroidery traditional culture. Objective： This article aims to deeply explore the inheritance and innovation paths of the intangible cultural heritage of Gu embroidery in the era of digital intelligence, thereby strengthening the protection and inheritance of Gu embroidery and promoting its modern development. Methods: This article, through literature analysis, explores the historical development of Gu embroidery and, by means of case analysis, clarifies its artistic value, thereby delving into the innovative paths for its modernization in the digital intelligence era. Results: In the era of digital intelligence, Gu embroidery, as a traditional skill, faces new opportunities and challenges. Intangible cultural heritage Gu embroidery is entering a new stage of digital intelligence integration, expanding the modern expression path of traditional skills. Conclusion: In the era of digital intelligence, not only does it inspire the creativity and design inspiration of Gu embroidery, enhance interactivity and participation, but it also increases public attention and protection of traditional Gu embroidery skills, making it play a key role in cultural exchange and dissemination.